Why and how must Portugal be synchronized with the European Union - Caleiro, António (2012)
A retrospective analysis of the Portuguese business cycle synchronization with some business cycles of reference allows us to draw conclusions that support the vital need to focus in domestic production that, by its nature, is exportable and/or is a substitute of imports. From this point of view, the increase in competitiveness, resulting from productivity growth, is also important given the gains derived from business cycle synchronization with the European business cycle obtained through the consequent increase in exports. This second aspect, less obvious but equally important for a sustained growth path, is the main focus of this chapter.